Substantial and Reproducible Individual Variability in Skeletal Muscle Outcomes in the Cross-Over Designed Planica Bed Rest Program - Fernandez-Gonzalo, Rodrigo; McDonnell, Adam C.; Simpson, Elizabeth J.; Macdonald, Ian A.; Rullman, Eric; Mekjavic, Igor B. (Frontiers in Physiology, 2021)
To evaluate the individual responses in skeletal muscle outcomes following bed rest, data from three studies (21-day PlanHab; 10-day FemHab and LunHab) were combined. Subjects (n=35) participated in three cross-over campaigns within each study: normoxic and hypoxic bed rest, and hypoxic ambulation (used as control). Individual variability (SDIR) was investigated as √(SDExp2–SDCon2), where SDExp and SDCon are the standard deviations of the change score (i.e., post - pre) in the experimental (normoxic and hypoxic bed rest) and the control (hypoxic ambulation) groups. Repeatability and moderators of the individual variability were explored. Significant SDIR was detected for knee extension torque, and thigh and calf muscle area, which translated into an individual response ranging from 3% to -17% for knee extension torque, -2% to -12% for calf muscle area, and -1% to -8% for thigh muscle area. Strong correlations were found for changes in normoxic vs. hypoxic bed rest (i.e., repeatability) in thigh and calf muscle area (r=0.65-0.75, P<0.0001). Change-scores in knee extension torque, and thigh and calf muscle area strongly correlated with baseline values (P<0.001; r between -0.5 and -0.9). Orthogonal partial least squares (OPLS) regression analysis explored if changes in the investigated variables could predict calf muscle area alterations. This analysis indicated that 43% of the variance in calf muscle area could be attributed to changes in all of the other variables. This is the first study using a validated methodology to report clinically relevant individual variability after bed rest in knee extension torque, calf muscle area, and (to a lower extent) thigh muscle area. Baseline values emerged as a moderator of the individual response, and a global bed rest signature served as a moderately strong predictor of the individual variation in calf muscle area alterations.